Comments on Risk Factors for Perforation in Endoscopic Treatment for Early Colorectal Cancer: A Nationwide ENTER-K Study - Fayuan Wang; Ping He (Gut and Liver)
Metabolic dysfunction-associated steatotic liver disease (MASLD) has emerged as one of the most prevalent chronic liver diseases globally, and its pathogenesis is closely linked to the imbalance of intestinal microbiota and their metabolites. This article reviews the mechanisms through which intestinal microbiota influence the progression of MASLD via the gut-liver axis, elaborating on the complex roles of immune cell hyperactivation, impaired intestinal barrier function, and intestinal microbial metabolites such as short-chain fatty acids and bile acids. The imbalance of intestinal microbiota not only directly promotes the development of MASLD but also further exacerbates disease progression through abnormalities in their metabolites. Various novel therapeutic strategies are being actively developed on the basis of gut-liver axis theory, including probiotic/prebiotic/synbiotic treatment, fecal microbiota transplantation, and targeted drug therapy. These strategies aim to precisely regulate microbial homeostasis and improve glucose and lipid metabolism, thereby alleviating hepatic inflammation and fibrosis and optimizing the therapeutic outcomes of patients with MASLD. In the future, as research progresses, we will further uncover the interaction mechanisms between intestinal microbiota and MASLD and continuously explore more effective treatment methods, with the goal of improving the prognosis and quality of life for MASLD patients.